The Distinct Impact of TAM Infiltration on the Prognosis of Patients With Cardia and Non-Cardia Gastric Cancer and Its Association With H. pylori Infection - Liu, Min; Zhang, Li; Zhou, Qiuru; Wang, Yuejie; Sun, Qian; Ren, Xiubao (Frontiers in Oncology, 2021)
Background: In stage III gastric cancer (GC), the role of tumor-associated macrophages (TAMs) and Helicobacter pylori (H. pylori) infection impact tumor progression; however, the specific mechanisms remain controversial. We speculated whether this controversy is caused by differences in the location of TAM infiltration (in the core (CT) and invasive margin (MI) of primary tumors) and the topographical subsites of GC (cardia and non-cardia). Therefore, in this study, we investigated TAMs in different locations and H. pylori infection status as prognostic biomarkers for GC. Methods: Immunohistochemical staining for CD68 (pan-macrophage), CD163 (M2-like macrophage), and H. pylori in 200 samples (100 cases of cardia-GC [CGC] and 100 cases of non-cardia GC [NCGC]) was performed. We compared the number of CD68+ and CD163+ macrophages that infiltrated the CT and MI in patient with the prognose of CGC and NCGC, respectively. In addition, we analyzed the relationship between H. pylori status and the prognosis of patients with GC in different locations, as well as the correlation with TAM infiltration. Results: The distribution of TAMs had distinct characteristics in CGC and NCGC, especially differences between CT and MI subtype. A Kaplan–Meier analysis showed that a high number of CD68+ macrophages that infiltrated the CT in CGC was associated with a better prognosis, whereas infiltration at the MI in NCGC indicated a poor prognosis. Furthermore, a high number of CD163+ macrophages infiltrating the MI resulted in a poor prognosis in CGC and NCGC cohorts. Considering the larger differences in the relationship between the infiltration of CD68+ macrophages at different locations and prognosis, we divided the GC cases into marginal and central GC, based on this difference. This resulted in an accurate estimation of the prognosis. Moreover, positive H. pylori status in central GC was significantly associated with a better prognosis and TAM infiltration. Conclusion: TAMs in different locations and H. pylori status were identified as independent prognostic markers, with an obvious correlation between them. Therefore, it is important to clarify the impact of TAM location on the prognosis of patients with GC, which contributes to the development of potential therapeutic strategies.